The Influence of Work Stress, Work-Life Balance, and Organizational Support on Auditor Resilience with Self-Efficacy as a Mediating Variable - Edwin Jonathan Panjaitan; Fauzi; Sheilla Amanda Putri; Tommy Munaf (IJMA (Indonesian Journal of Management and Accounting), 2026)
ABSTRACT This research seeks to explore the impact of work stress, work-life balance, and organizational support on the resilience of auditors, with self-efficacy acting as a mediating factor. A quantitative research strategy utilizing a survey format was adopted, engaging auditors from public accounting firms. The data were assessed through multiple regression, t-tests, Sobel mediation assessments, and F-tests. The main results show that organizational support has a significant effect on auditor resilience both directly and through self-efficacy. Self-efficacy also has a strong direct relationship with resilience. In contrast, work stress does not have a direct effect on resilience but has a significant indirect effect through the mediation of self-efficacy. Meanwhile, work-life balance does not show a significant direct or indirect effect on resilience. Collectively, the three independent variables (work stress, work-life balance, organizational support) are only able to explain a small portion of the variance in resilience. However, when self-efficacy is included in the model, the model's predictive ability increases substantially. The study's empirical contribution lies in demonstrating that self-efficacy serves as a crucial mediator, particularly in converting work stress into resilience. A novel aspect of this study is its finding that work-life balance does not serve as a factor influencing auditor resilience, which contradicts typical beliefs in different professions. For public accounting firms, the implication involves emphasizing organizational support and self-efficacy development instead of focusing on work-life balance initiatives to improve auditor resilience during busy periods.   ABSTRAK Penelitian ini bertujuan untuk mengeksplorasi dampak stres kerja, keseimbangan kerja-hidup, dan dukungan organisasi terhadap ketahanan auditor, dengan efikasi diri sebagai faktor mediasi. Strategi penelitian kuantitatif yang menggunakan format survei diadopsi, melibatkan auditor dari firma akuntansi publik. Data dianalisis melalui regresi berganda, uji-t, penilaian mediasi Sobel, dan uji-F. Hasil utama menunjukkan bahwa dukungan organisasi memiliki pengaruh signifikan terhadap ketahanan auditor baik secara langsung maupun melalui efikasi diri. Efikasi diri juga memiliki hubungan langsung yang kuat dengan ketahanan. Sebaliknya, stres kerja tidak memiliki pengaruh langsung terhadap ketahanan tetapi memiliki pengaruh tidak langsung yang signifikan melalui mediasi efikasi diri. Sementara itu, keseimbangan kerja-hidup tidak menunjukkan pengaruh langsung atau tidak langsung yang signifikan terhadap ketahanan. Secara kolektif, ketiga variabel independen (stres kerja, keseimbangan kerja-hidup, dukungan organisasi) hanya mampu menjelaskan sebagian kecil varians dalam ketahanan. Namun, ketika efikasi diri dimasukkan ke dalam model, kemampuan prediksi model meningkat secara substansial. Kontribusi empiris studi ini terletak pada demonstrasi bahwa efikasi diri berperan sebagai mediator penting, khususnya dalam mengubah stres kerja menjadi ketahanan. Aspek baru dari studi ini adalah temuannya bahwa keseimbangan kerja-hidup tidak berperan sebagai faktor yang memengaruhi ketahanan auditor, yang bertentangan dengan keyakinan umum di berbagai profesi. Bagi firma akuntansi publik, implikasinya adalah menekankan dukungan organisasi dan pengembangan efikasi diri daripada berfokus pada inisiatif keseimbangan kerja-hidup untuk meningkatkan ketahanan auditor selama periode sibuk.